Active Interaction Design for Stress Therapy Virtual Environment - Zaharuddin F.A.; Ibrahim N.; Yusof A.M.; Mohd Mahidin E.M.; Rusli M.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Stress relief; 3-D environments; Design elements; Interaction design; Pilot studies; Virtual reality technology; Virtual reality